1999
DOI: 10.1097/00007435-199901000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Self-Reported Sexual Histories: Test-Retest and Interpartner Comparison in a Sexually Transmitted Diseases Clinic

Abstract: The authors conclude that data on sexual behavior can be collected reliably among sexually transmitted disease clinic attendees, although reporting bias does occur. The frequency of sexual intercourse was not sufficiently reliable and should be interpreted as an estimate only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…A further limitation of this study is the use of self-reported measures of behavior. However, the reliability of self-reported condom use has been established by the use of test-retest reliability analyses and validation of self-reported condom use against sexual partners' reports (Jeannin et al, 1998;Mathias et al, 1999;Van Duynhoven et al, 1999) and seroconversion (De Vincenzi, 1994;Shew et al, 1997). Finally, because this study was cross-sectional, causal direction can be only plausibly inferred.…”
Section: Discussionmentioning
confidence: 94%
“…A further limitation of this study is the use of self-reported measures of behavior. However, the reliability of self-reported condom use has been established by the use of test-retest reliability analyses and validation of self-reported condom use against sexual partners' reports (Jeannin et al, 1998;Mathias et al, 1999;Van Duynhoven et al, 1999) and seroconversion (De Vincenzi, 1994;Shew et al, 1997). Finally, because this study was cross-sectional, causal direction can be only plausibly inferred.…”
Section: Discussionmentioning
confidence: 94%
“…One study of men found high reliability (у90% agreement) between responses to questions on sexual activity reported for the previous 2 weeks and the previous 3 months but not between those shorter periods and the previous year [28]. In another study, test-retest agreement was also strong for age at first intercourse (86%) and lifetime number of sex partners (82%) [29]. Because most questions included in the present study asked men to reflect on lifetime questions or activities during the past 3 months, confidence is increased for reliability of responses.…”
Section: Discussionmentioning
confidence: 99%
“…The general finding is one of very high levels of test-retest reliability in population surveys 29 and in such diverse populations as STI clinic attenders, 30 residential drug treatment populations, 31 adolescents as young as 14 years of age 32 and psychiatric patients. 33 Good test-retest reliability has been demonstrated over periods up to 18 months apart.…”
Section: Obtaining a Representative Samplementioning
confidence: 97%
“…26 The reliability of self-report is supported by high levels of agreement in the reports of sexual activity between the sexual partners. 30,[35][36][37][38] In one American clinic population, partner reports of sexual activity and condom use were not found to be highly consistent. 39 The validity of self-reported sexual behaviour is difficult to ascertain.…”
Section: Obtaining a Representative Samplementioning
confidence: 99%